Superior Medullary Velum: Anatomical-Histological Study in the Sheep Brain and a Preliminary Tractographic Study in the Human Brain - (:unkn) unknown (TURKISH NEUROSURGICAL SOC, 2013)
AIM:To study the anatomy, histology and fiber relations of the superior medullary velum. MATERIAL and METHODS: Ten previously frozen and formalin-fixed sheep brains were used. The fiber dissection was done using the operating microscope at the Rhoton Anatomy Laboratory of Marmara Faculty of Medicine. A tractographic study was conducted on five volunteer patients to see the fiber anatomy of the superior medullary velum. RESULTS: The average thickness and length was found to be 0.296 mm (range 0.09-1 mm) and 4.25 mm (range 3.25-4.5 mm) respectively. Histologically, the superior medullary velum consisted of cuboidal layer of ependymal cells on the anterior surface related to fourth ventricle. The subependymal layer contained hypocellular fibrillary zone with few glial cells, and the outer layer consisted of thin layer of fibroblasts. Under the hypocellular fibrillary zone, abundant axons and organized structures were observed. Tractographically, only a few fibers were identified on diffusion-tensor imaging (DTI). CONCLUSION: We could not identify a distinct tract anatomically and neuron cells histologically. Neuron-like cells and organized structures were observed on immunohistochemical analysis. Also a few tracts were observed on DTI study as an ascending pathway from spinal tracts to the superior medullary velum. Further studies including human cadaveric, histologic and fiber tractographic investigations are needed to say that it is harmless to divide this anatomical structure.
Keywords: Anatomy; Fiber dissection; Histology; Sheep; Superior medullary velum; Tractography; MICRO-SURGICAL ANATOMY; 4TH VENTRICLE; NERVE-FIBERS; RAT; 4TH-VENTRICLE; HYDROCEPHALUS; REGENERATION; MUSCLES; TUMORS